Gout of the Temporomandibular Joint: Report of a Case - Oliveira, Isaac Nilton Fernandes; Gomes, Renata Caroline Ferreira; dos Santos, Raiane Rodrigues; Oliveira, Thiago de Paula; Pereira, Larissa Loiuse Cândida; Mainenti, Pietro (International Archives of Otorhinolaryngology, 2014)
Introduction Gout is an illness characterized by the deposition of monosodium urate crystals in the joints or in soft tissues. The clinical manifestation results from inflammation of limb joints and pain with a rare presentation in the temporomandibular joint (TMJ).Case Report This study describes a 66-year-old white man with a chief complaint of “occasional pain in the left temporal muscle region.” The case disclosed a gout manifestation in the TMJ after physical, radiographic, and ultrasonographic exams, and the patient was referred to proper treatment.Conclusion Gout manifestation in the TMJ is an unusual presentation, and few reports in the English literature address to the subject. Gout in the TMJ should be included as a differential diagnosis for joint disorders.
Keywords: gout; temporomandibular joint; joint diseases